Desenvolvimento de um sistema de movimentação e fixação para galpão metálico industrial - Trindade, Arielton Vinícius (2016)
For optimize the use of important areas in shipyards and improve the working conditions of people who are exposed to the weathers, companies are constantly looking to improve the layout of their factories and avoid the cost of idle hand work. Normally used in the manufacture of parts and assembly of large equipment in shipyards, traditional metal sheds, ie fixed in a certain place without the possibility of relocation, unless there disassembly and reassembly at the desired location. Within this context, mobile metal sheds with displacement linear, become an interesting option, as they allow the assembly of large components in a covered place without the need for disassembly and reassembly. Through this need, using a methodology for product development of the authors Pahl and Beitz is conceived a variant solution for displacement linear and fixing along a certain path to metallic shed. Through this possible solution of the problem of the project are develop the calculations of the efforts active in the bases of the moving metallic shed, of the activation of the system by traditional methods and the structural validation of the set of fixation through the analysis in finite elements, where the most critical situation found in the simulations is the result of simultaneous application of the moment, shear effort and axial effort, where the mechanism designed for the solution of the design problem, supports the maximum effort of 1.141 kN.m before collapsing.